2021
DOI: 10.1016/j.jseint.2020.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Similar scapular morphology in patients with dynamic and static posterior shoulder instability

Abstract: Background There is evidence that specific variants of scapular morphology are associated with dynamic and static posterior shoulder instability. To this date, observations regarding glenoid and/or acromial variants were analyzed independently, with two-dimensional imaging or without comparison with a healthy control group. Therefore, the purpose of this study was to analyze and describe the three-dimensional (3D) shape of the scapula in healthy and in shoulders with static or dynamic posterior in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Analogous to other studies, we also found an increased incidence of glenoid retroversion in the patients with B2 instability. 5 , 15 , 17 , 19 , 31 The median glenoid version of all patients measured with the vault method was 14.8°. Meanwhile, the glenohumeral index was normal being 52% ( Table II ).…”
Section: Discussionmentioning
confidence: 97%
“…Analogous to other studies, we also found an increased incidence of glenoid retroversion in the patients with B2 instability. 5 , 15 , 17 , 19 , 31 The median glenoid version of all patients measured with the vault method was 14.8°. Meanwhile, the glenohumeral index was normal being 52% ( Table II ).…”
Section: Discussionmentioning
confidence: 97%
“…Our case is in agreement with the experimental data and documents that correction of scapular anatomy can restore normal glenohumeral congruity in SPSL in vivo. Given the similarity of scapular pathology in static and dynamic posterior instability 22 , quantitative correction of the anthropometric abnormalities of the scapula may open a new way for the understanding and treatment of posterior shoulder instability. n…”
Section: Discussionmentioning
confidence: 99%
“…Although Walch et al stated that static posterior subluxation of the humeral head preceded posterior glenoid wear, with glenoid retroversion as a risk factor [11,13], there is currently no consensus regarding this chicken-or-egg debate [6,14,15]. To our knowledge and despite the recent study by Beeler et al [10], there are no published data on the correlation between the detailed three-dimensional (3D) acromion shape and glenoid retroversion.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Meyer et al were able to link a decreased posterior acromion slope and increased glenoid retroversion with static posterior subluxation of the humeral head and posterior glenoid wear [9]. More recently, Beeler et al reported that the scapula of a shoulder with dynamic and static posterior instability was characterized by an increased glenoid retroversion and an acromion that was shorter posterolaterally and higher and more horizontal in the sagittal plane [10].…”
Section: Introductionmentioning
confidence: 99%